Stock market conditions and monetary policy in an DSGE model for the US - Efrem Castelnuovo; Salvatore Nisticò (Bank of Finland, 2010)
We improve the precision of the test of the implicit contract model that Beaudry and DiNardo proposed twenty years ago. Our data set allows us to define the precise industry and plant of a particular employment relationship, link local labour market characteristics and company characteristics to the individual level of wages, and control for composition effects. We find evidence in favour of the spot market model of wage setting in the whole sample, but there is significant variation across industries and educational levels. In particular, the spot market matters most for low-skill workers, while the implicit contract model with one-sided limited commitment applies better to high-skill workers.
URN:NBN:fi:bof-20140807609
Keywords: 330